The Types of Cohesion Used in the ‘Issues of the Day’ Strip in the Jakarta Post - Wulan Agustina (Register Journal, 2015)
This study is aimed at describing discourse studies especially at cohesion from reader’s opinion strip. This is literary research, so the writer uses descriptive qualitative approach. In this research, documentation and note taking technique are used to collect the data. There are two objectives of the research: 1) to carry out the types of grammatical cohesion used in the “Issues of the Day” strip in The Jakarta Post on March 2012 edition and 2) to find out the types of lexical cohesion used in the “Issues of The Day” strip in The Jakarta Post on March 2012 edition. After investigating the English sentences used in the “Issues of the Day” strip in The Jakarta Post on March 2012 edition, the writer found several findings as follows: 1) based on the analysis of grammatical cohesion, the writer found there are references, substitutions, ellipsis, and conjunctions; 2) based on the analysis of lexical cohesion, the writer found repetitions, synonyms, hyponyms, meronyms, antonyms, and collocations. The writer expects that it is able to contribute the science of linguistic and able to be guidance for all readers.Keywords:cohesion;   ‘Issues of the Day’ strip